Lymph node dissection: XXV Congreso Uruguayo de Cirugía; coordinator Alberto Valls - Valls, Alberto; Praderi, Raúl C.; Trotschansky, José; Sarroca, Carlos; Mérola, Lorenzo; Liard, Washington; Morelli Brum, Raúl; Durante Barbot, Arturo (Cirugía del Uruguay, 1975)
Lymph node dissections are operations used in oncological surgery, complementary to visceral removal, with the primitive tumor, based on the notion of predominantly lymphatic spread of tumorsepithelial malignant. Although blood dissemination is more important in those of conjunctival lineage, as that modality also exists in them, these ir are applied to them; interventions, also applicable to primitive lymphatic tumor lymphopathies.